The Teacher’s Presence in Online Learning Community - Kwiatkowska, Wioletta; Skibińska, Małgorzata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
This paper reports the results of a survey study aimed at diagnosing the presence of teachers in the educational space of the Internet. The theoretical basis for the considerations are the assumptions of the pedagogy of place. It implies the ability to create new places of learning, including the world of the cyberspace, so often used by students. The question of the presence of the teacher on the Internet has become an important issue in pedagogical sciences, and in the wider field of social science. 182 Polish teachers from the Kuyavian-Pomeranian region participated in the described study. The obtained data allowed to indicate “Internet places” frequently visited by the surveyed teachers, to determine their interests for supplementing and updating their digital competences using forms of e-learning, for the cultural and creative activities and promoting their creations and exchange of experience on the Internet with particular emphasis on social media. The conclusions contain important premises for educational practice indicating the need to take pedagogical reflection by the teacher and to run concrete actions promoting humanistic values, to support students’ online activities, to make them aware of the importance of critical thinking and conscious and responsible publication of the content on the Internet. As it turns out, the surveyed teachers want to be present on the Internet, use its resources and communication services; unfortunately, their involvement in the pedagogisation of the Internet space and the promotion of their own substantive and methodological achievements in the cyberspace is still minor